EPV 6. Value of transcranial brain stem sonography in the diagnosis and prognosis of amyotrophic lateral sclerosis. Issue 9 (September 2016) - Schenk, A.; Günther, A.; Prell, T.; Ringer, T.M.; Gunkel, A.; Stubendorff, B.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: Amyotrophic lateral sclerosis (ALS) is a severe motor neuron disease, most common in adult-onset, characterized by a progressive failure of upper and lower motor neurons. Symptoms of lower motor neuron disease such as progressive atrophic weakness may obscure upper motor neuron signs so that the correct diagnosis and initiation of treatment may be delayed. Objective: The aim of the study was to evaluate the usefulness of transcranial brain stem sonography (TCS) as additional diagnostic tool in ALS and discussed the prognostic value. Material and methods: 94 patients with sporadic ALS and 46 age- and gender- matched healthy controls were studied with TCS according to a standardized protocol used in Parkinson patients. The observed hyperechogenic changes in the mesencephalon were categorized depending on their size into three groups („clear" > 0.25 cm[b], „possible" < 0.25 cm[b], „no"). Results: 48% of the ALS-patients and 2% of healthy controls showed a clear mesencephalic hyperechogenic structure ( p < 0, 001). 20% of ALS-patients and 4% controls showed possible and 24% ALS-patients and 78% showed no hyperechogenic structures in the brainstem. TCS findings did not correlate with gender, disease onset (spinal, bulbar), disease duration, disease severity (ALSFRS-R), motor evoked potentials (MEP), and MRT results. Conclusion: TCS could serve as an additional diagnostic tool in ALS in order to improve early diagnosing. We detected significantly more hyperechogenicities in the anatomical area of the pyramidal fibre tract in the mesencephalon of ALS patients compared to healthy controls. Although the neuropathological correlate is unclear, the observed changes reflect upper motor neuron degeneration in pyramidal tract, proliferation of glial cells and extracellular matrix damage. To assess the value of TCS as a diagnostic and prognostic marker in ALS, further cross-sectional and longitudinal studies are necessary, especially retrospective observation of disease-progression. Acknowledgement: This study was supported by a grant to JG by the BMBF through the E-RARE framework and in collaboration with the German Network for Motoneuron Diseases (MND-NET).